Iatrogenic atrial septal defect following transseptal cardiac interventions. (15th April 2016) - Alkhouli, Mohamad; Sarraf, Mohammad; Zack, Chad J.; Holmes, David R.; Rihal, Charanjit S.
Abstract: In the Era of expanding use of transseptal structural heart disease interventions and catheter ablation techniques for atrial fibrillation, there is increasing interest in the iatrogenic atrial septal defect (iASD) often associated with these procedures. The purpose of this review is to summarize the current evidence on the incidence and clinical impact of iASD, to identify possible predictors of persistent iASD, and to propose a standardized method for the detection, follow up and management of iASD. Highlights: Persistent iASD after transseptal procedures are not uncommon, especially when larger TS sheath are used. The current literature is inconclusive with regard to the clinical signficance of persistence iASD. Routine surveillance of patients with iASD might be necessary. Selective closure of the iASD should be considered in high risk patients.